2012
DOI: 10.1093/cid/cis929
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Spectrum β-Lactamase–Producing Escherichia coli From Retail Chicken Meat and Humans: Comparison of Strains, Plasmids, Resistance Genes, and Virulence Factors

Abstract: We found significant genetic similarities among ESBL-EC isolates from chicken meat and humans according to mobile resistance elements, virulence genes, and genomic backbone. Therefore, chicken meat is a likely contributor to the recent emergence of ESBL-EC in human infections in the study region. This raises serious food safety questions regarding the abundant presence of ESBL-EC in chicken meat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
157
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(176 citation statements)
references
References 31 publications
6
157
1
3
Order By: Relevance
“…This finding is supported by data from our study: 50% of participants who had a positive pretravel sample had traveled during the previous 12 months. This high percentage of carriers identified in this study before travel points toward ongoing importation of ESBL-E. Other potential reservoirs for ESBL-E are poultry and other retail meats, which have been found to be contaminated with ESBL-producing E. coli strains harboring the genes on identical plasmids as found in human isolates ( 15 , 16 ). …”
Section: Discussionmentioning
confidence: 63%
“…This finding is supported by data from our study: 50% of participants who had a positive pretravel sample had traveled during the previous 12 months. This high percentage of carriers identified in this study before travel points toward ongoing importation of ESBL-E. Other potential reservoirs for ESBL-E are poultry and other retail meats, which have been found to be contaminated with ESBL-producing E. coli strains harboring the genes on identical plasmids as found in human isolates ( 15 , 16 ). …”
Section: Discussionmentioning
confidence: 63%
“…On the other hand, the use of antimicrobial agents in animal production has caused an increase in the resistance of Enterobaceriaceae and other bacterial families, with higher production of β-lactamases, which hydrolyze the β-lactam ring and inactivate the β-lactams [28]. The results are a high prevalence of extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae in meat products.…”
Section: Resultsmentioning
confidence: 99%
“…The IncI1, IncFIB, IncY and IncN plasmids have been identified in poultry previously and were associated with MDR and ESBLs producing E. coli (Bortolaia et al, 2010;Garcia-Fernandez et al, 2008;Kluytmans et al, 2013;Lynne et al, 2012;Seni et al, 2016;Wang et al, 2013a). One of the ESC resistant isolates contained IncY and IncI1 plasmid types, while the other contained IncFIA, IncFIB and IncFrep plasmids.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have reported that plasmids contribute to the transfer of resistance genes among E. coli isolates (Jones-Dias et al, 2015;Kluytmans et al, 2013). Carattoli et al (2011) described an association between certain types of plasmids and resistance genes such as bla DHA-1 (an AmpC β-lactamase) and plasmid type IncF.…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation